PREVALENCE AND RISK FACTORS OF DIABETES MELLITUS IN TUBERCULOSIS PATIENT AT PATRANG DISTRICT INDONESIA - Sasmita, Hasri Yulia; Prasetyowati, Irma; Wahjudi, Pudjo (Institute of Topical Disease Universitas Airlangga, 2019)
Tuberculosis (TB) is one of cause of death in infectious disease domain. The control of TB is complicated because the inclination of case numbers people with Diabetes Mellitus. Diabetes Mellitus (DM) is an important risk factor for TB development, with prove that more than ten percent of TB patient is DM patient. People with DM have risk three times more likely to suffer from TB than people without DM. The results of TB treatment with comorbid DM will be easier to be failed. Puskesmas Patrang have the highest bacteriologically confirmed BTA TB cases and DM cases in Jember during 2014 until 2016. The aim of this research is to know the DM prevalence in TB patients and to analyze the correlation between DM risk factors in TB patient to TB-DM incidence at Puskesmas Patrang Jember in 2017. The research uses observasional analytic with cross sectional approach. The sampling technique uses simple random sampling with 47 samples. The independent variables include respondent characteristics (age, sex, type of TB, medication category, and family history of DM), central obesity and smoking behavior. While the dependent variable is the DM status. The result shows that the prevelance of DM in TB patients at Puskesmas Patrang Jember regency is 23,4%. Factors associated with TB-DM are age (p-value = 0,012), family history of DM (p-value = 0,003), and smoking status (p-value = 0,035). Factors that do not associated with TB-DM are sex (p-value = 0,731), type of TB (p-value = 0,170), treatment category of TB (p-value = 0,560), central obesity (p-value = 0,435), the number of cigarette (p-value = 1,000) and smoking duration (p-value = 1,000). The most important factor of TB-DM is family history of DM that 10,850 times higher of getting TB-DM than patients without family history of DM.